NILAI RANTAI DISTRIBUSI KOMODITAS GABAH DAN BERAS DI KABUPATEN BATANG - Muhammad Sobichin (Economics Development Analysis Journal, 2012)
Disparity between the price of grain and rice prices are very high causing the welfare of farmers declined, given the 60 percent of farmers are net producer and consumer of rice. In an effort to narrow the disparity between the price of grain at the farm level and rice prices at the consumer level in Batang, it is necessary to study the system of commodity marketing and rice. Specifically, the study aims to: (i) describe the distribution patterns and rice, and (ii) analyze the marketing margin on each offender marketing. The results are expected to be material in the design of the distribution patterns of policy alternatives and rice especially in Batang. What research determined accident in three rice-producing centers in the District of Batang. The study was conducted in July-August 2012 to 60 farmers, 15 traders, 10 rice mills, five wholesalers and 10 retailers through snowball sampling technique. Data were analyzed by descriptive of the patterns of distribution and marketing margins and rice. The results are in Batang there are four patterns of distribution, first; farmer middlemen -> mills wholesaler -> retailer -> consumer, secondly, farmers traders -> mills retailer -> consumer; Third, farmers milling -> Rice -> wholesaler -> retailer -> consumer; fourth, farmers mills -> retailer -> consumer. Marketing margins were highest in the rice mill at 47.4 percent, then traders 4.9 percent, 4.2 percent wholesalers, and retailers 3.3 percent of the total value of grain and rice marketing margins. Suggestions in this study, namely: (i) farmers must optimize the role of farmer groups in post-harvest and marketing of rice yields in an integrated and coordinated. Merging farmers in the group will strengthen the bargaining power of the actors and rice trade system.(ii) in the short term the government should encourage farmers to sell grain in the form of Dry Milled Rice (MPD), so it has a value-added commodity and the price did not fall during the harvest. Therefore the government must develop a granary and drying facilities in rural areas. This will shorten the marketing chain, which is expected to reduce the disparity between the prices of grain and rice prices.